Clinical and Radiologic Outcomes of Submerged and Nonsubmerged Bone‐Level Implants with Internal Hexagonal Connections in Immediate Implantation: A 5‐Year Retrospective Study. Issue 2 (16th November 2017) - Wu, Shiyu; Wu, Xiayi; Shrestha, Rachana; Lin, Jinying; Feng, Zhicai; Liu, Yudong; Shi, Yunlin; Huang, Baoxin; Li, Zhipeng; Liu, Quan; Zhang, Xiaocong; Hu, Mingxuan; et al.
Abstract: Purpose : To evaluate the 5‐year clinical and radiologic outcome of immediate implantation using submerged and nonsubmerged techniques with bone‐level implants and internal hexagonal connections and the effects of potential influencing factors. Materials and Methods : A total of 114 bone‐level implants (XiVE S plus) with internal hexagonal connections inserted into 72 patients were included. Patients were followed up for 5 years. A t ‐test was used to statistically evaluate the marginal bone loss between the submerged and nonsubmerged groups. The cumulative survival rate (CSR) was calculated according to the life table method and illustrated with Kaplan‐Meier survival curves. Comparisons of the CSR between healing protocols, guided bone regeneration, implants with different sites, lengths, and diameters were performed using log‐rank tests. Results : The 5‐year cumulative implant survival rates with submerged and nonsubmerged healing were 94% and 96%, respectively. No statistically significant differences in terms of marginal bone loss, healing protocol, application of guided bone regeneration, implant site, or length were observed. Conclusions : High CSRs and good marginal bone levels were achieved 5 years after immediate implantation of bone‐level implants with internal hexagonal connections using both the submerged and nonsubmerged techniques. Factors such as implant length, site, and application of guided bone regeneration did not have an impact on the long‐term success of the implants.